GENERAL ASPECTS REGARDING THE INTERNAL CONTROL OF ASSETS IN THE MINING SECTOR - BOGDAN RĂVAŞ (Annals of the University of Petrosani: Economics)
In certain situations, the improper operations are obvious, for example, the unauthorized acquisition by employees of personal goods or, more importantly, theft of money by recording a fictitious purchase in the purchase log, remains the concern of high level management, which can avoid certain internal rigor. If the control mechanisms aimed at detecting inappropriate or non-existent operations are inadequate, then a thorough examination of the supporting documents, inspection of the respective assets is required.